3D Transmissibility and Relative Transmissibility of Immobilized Supine Humans during Transportation. Issue 2 (June 2014) - Meusch, John; Rahmatalla, Salam
The three-dimensional translational multi-input/output relative transmissibility and the transmissibility of supine humans during transportation were introduced in this work and were compared with the single-axis input/output condition. Eight healthy subjects were tested under multi-axis input/output whole-body vibration of white noise random signals with frequency content of 0.5–20 Hz and vibration magnitude of 1 m/s 2 RMS applied at the platform level, considering three immobilization conditions: rigid-platform, litter-board, and litter-board-collar. The results showed the diagonal components of the multi-axis input/out transmissibility and relative transmissibility to be considerably larger than their out-of-diagonal components. Significant correlations (R 2 > 0.93) were found between the diagonal components of the transmissibility of the multi-axis input/output and those of the individual single-axis input/output whole-body vibrations; however, weaker correlation (R 2 > 0.11) was shown between their cross-axis components.